2022
DOI: 10.3390/app12020909
|View full text |Cite
|
Sign up to set email alerts
|

A Fluid Inclusion and Critical/Rare Metal Study of Epithermal Quartz-Stibnite Veins Associated with the Gerakario Porphyry Deposit, Northern Greece

Abstract: The Gerakario Cu-Au porphyry deposit in the Kilkis ore district, northern Greece, contains epithermal quartz-stibnite veins on the eastern side of the deposit, which crosscut a two-mica gneiss. Metallic mineralization in these veins consists of stibnite + berthierite + native antimony + pyrite + arsenopyrite, and minor marcasite, pyrrhotite, chalcopyrite, löllingite, and native gold. Bulk geochemical analyses of the ore reveal an enrichment in critical and rare metals, including Ag, Au, Bi, Ce, Co, Ga, La, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
(80 reference statements)
0
0
0
Order By: Relevance
“…Older peridotite-serpentinite from the Triassic age, which belongs to the Serbo-Macedonia Massif (Vertiskos unit), are found nearby. According to Stergiou et al [94] the A-type veins found in the porphyry-style mineralization exhibit fluid inclusions that indicate fluid boiling. This process led to the formation of a highly saline aqueous fluid phase (with a concentration of 35.7 to 45.6 wt.% NaCl equivalent) and a moderately saline gas phase (with a concentration of 14 to 22 wt.% NaCl equivalent) within the H 2 O-NaCl-KCl system.…”
Section: Gerakariomentioning
confidence: 99%
See 2 more Smart Citations
“…Older peridotite-serpentinite from the Triassic age, which belongs to the Serbo-Macedonia Massif (Vertiskos unit), are found nearby. According to Stergiou et al [94] the A-type veins found in the porphyry-style mineralization exhibit fluid inclusions that indicate fluid boiling. This process led to the formation of a highly saline aqueous fluid phase (with a concentration of 35.7 to 45.6 wt.% NaCl equivalent) and a moderately saline gas phase (with a concentration of 14 to 22 wt.% NaCl equivalent) within the H 2 O-NaCl-KCl system.…”
Section: Gerakariomentioning
confidence: 99%
“…The Sb-mineralization mostly comprises arsenopyrite, pyrite, berthierite, stibnite, native antimony, and pyrrhotite, with small occurrences of marcasite, chalcopyrite, löllingite, and native gold [94,95]. The occurrence of native Sb indicates that the fluids were supersaturated with respect to antimony.…”
Section: Gerakariomentioning
confidence: 99%
See 1 more Smart Citation
“…The intrusion-related mineralization includes polymetallic assemblages hosted in quartz veins and/or metamorphic rocks that are enriched in Cu-As-Pb-Bi-Ag-Au-Te or in Sb-W [6,10,11]. Significant polymetallic mineralizations are located across the Vertiskos unit at Laodikino, Koronouda, Stefania-Paliomylos, Kolchiko, Drakontio, and Stanos, while the Sb-W mineralization can be found at Rizana and Philadelphio (Figure 1).…”
Section: Geological Settingmentioning
confidence: 99%
“…Table 1. Overview of the typology, alteration, and textural characteristics of the hypogene mineralization hosted in major vein-type deposits found at the Vertiskos unit (data compiled from [5][6][7][8][9][10][11]13,14]). Based on ore assemblages, mineral chemistry, and fluid inclusion studies, two stages of magmatic-hydrothermal activity are mainly documented: an early, higher-temperature stage rich in Fe-As with arsenopyrite-and pyrite-dominated polymetallic massive veins and a later, lower-temperature stage related to the polymetallic quartz veins enriched in Bi-sulfosalts and tellurides.…”
Section: Major Cenozoic Vein-type Mineralization and Critical Metal D...mentioning
confidence: 99%